Implementation of an improved cellular neural network algorithm for brain tumor detection - Azian Azamimi, Abdullah; Bu, Sze Chize; Nishio, Yoshifumi (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/